Pengaruh Strategi Jigsaw terhadap Kemampuan Komunikasi Siswa - Rahmawati, Adelia; Ningsih, Yulli Mulia; Azmi, Wildan; Yana, Nur Elyda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Communication skills in students during the teaching and learning process are very important for a teacher to pay attention to. With good communication, a good learning process is also established. The purpose of this research is to analyze the influence of the jigsaw method on students' communication skills. The research method used in this study is an experimental method, with the population being classes VA and VB. The method used in this research is requirements testing, where the researcher conducted tests for homogeneity, normality, and distribution. The results of the research found that using the jigsaw method in the learning process has a significant impact on students' communication skills.